Sound Design in Popular Music: Gen Z Perspective and Perception - Ferdian, Robby; Hidayat, Hengki Armez; Sari, Ayuthia Mayang; Putra, Irdhan Epria Darma; Fitria, Ressy; Fauzi, Fakhri; Lailiyah, Malikhatul (Program Magister Teknologi Pendidikan Universitas Jambi, 2025)
This study explores Generation Z's understanding and perception of sound design in popular music, focusing on how this concept influences their music-listening experiences and emotional responses. Sound design, encompassing audio production quality, sound effects, and waveform processing, is critical in shaping diverse auditory experiences. However, the depth of understanding of sound design among Generation Z varies widely, presenting an opportunity to bridge knowledge gaps in music education. Using a quantitative descriptive approach, a survey was conducted among students with music education backgrounds to assess their familiarity with sound design concepts. The findings reveal diverse levels of comprehension, with some respondents recognizing the term